EVALUATING THE RISK OF OSTEOPOROSIS THROUGH BONE MASS DENSITY - Sayed, Sayeeda Amber; Khaliq, Asif; Mahmood, Ashar (Journal of Ayub Medical College Abbottabad, 2016)
Background: Osteoporosis is a bone disorder, characterized by loss of bone mass density. Osteoporosis affects more than 30% of post-menopausal women. Osteoporosis is often associated with restricted body movement, pain and joint deformities. Early identification and early intervention can help in reducing these complications. The primary objective of this study was to estimate the burden of Osteoporosis in Urban setting of Sindh among women of different age groups and to access the effect of different protective measures that can reduce the risk of Osteoporosis. Method: In this study, 500 women’s of 3 major cities of Sindh were approached by non-probability convenience sampling technique. Women bearing age 20 years or more were included. Women who fall under inclusion criteria were screened for BMD (Bone mineral density) test and were classified as Healthy, Osteopenic and Osteoporotic based on their T-score. The association of different protective measures and risk of osteoporosis was assessed by prevalence relative risk (PRR). Result: The result of this study indicate that the burden of Osteoporosis is very high among the women of Sindh, only 17.4% (84) women were found to have normal BMD score. The life style of majority of women was sedentary. The PRR calculated for Exposure to sunlight, regular exercise, and use of nutritional supplement was 12.5, 5.19 and 2.72 folds respectively. Conclusion: The results of study reveal that exposure to sunlight, regular physical exercise and use of nutritional supplements found to be effective in reducing the risk of osteoporosis among women of all age group. Health education and promotion toward osteoporosis prevention can significantly contribute in reducing the morbidity of osteoporosis. Keywords: Osteoporosis; Bone Mineral Density; Risk